WMS, APIs and LibGuides: Building a Better Database A-Z List - Ramshaw, Veronica (2018)
At the American University of Sharjah, our Databases by title and by subject pages are the 3rd and 4th most visited pages on our website. When we changed our ILS from Millennium to OCLC’s WorldShare Management Services (WMS), our previous automations which kept our Databases A-Z pages up-to-date were no longer usable and needed to be replaced. Using APIs, a Perl script, and LibGuides’ database management interface, we developed a workflow that pulls database metadata from WMS Collection Manager into a clean public-facing A-Z list. This article will discuss the details of how this process works, the advantages it provides, and the continuing issues we are facing.